Hubungan Konflik Peran Ganda, Status Pernikahan, Usia, dan Lama Bekerja dengan Stres Kerja pada Pekerja Wanita - Heriziana Hz; Shanti Rosalina (Jurnal Sains dan Kesehatan, 2026)
Work stress is a critical occupational health concern among midwives working at primary healthcare facilities. This cross-sectional study aimed to analyze factors associated with work stress among 30 midwives, including age, marital status, length of service, and dual-role conflict. Data were collected using structured questionnaires measuring work stress (9 valid items) and dual-role conflict (6 items), and analyzed through univariate, bivariate (Fisher's Exact Test and Chi-Square), and multivariate (binary logistic regression) analyses. Results showed that 43.3% of midwives experienced high work stress and 53.3% reported high dual-role conflict. Bivariate analysis revealed significant associations between work stress and marital status (p=0.009) and dual-role conflict (p=0.004), while age (p=0.633) and length of service (p=0.586) were not significant. Multivariate analysis identified dual-role conflict as the primary determinant of work stress (OR=15.762; 95% CI: 2.149–115.631; p=0.007). Healthcare facility management should develop gender-responsive policies and workplace stress intervention programs to reduce dual-role conflict and work stress among midwives.